Asymmetric Synthesis of cis-(S,R)-3-Amino-4-fluoro-1-methylpyrrolidine - Fei, Zhongbo; Xiong, Xin; Cheung, Chiming; Liu, Weipeng; Shen, Qirong; Zhang, Jinzhu; Gao, Hongjun; Bian, Jianwei (Synlett, 2019)
The development of the stereoselective synthesis of cis-(S,R)-3-amino-4-fluoro-1-methylpyrrolidine is described starting from chiral, non-racemic 1-[(3S,4S)-3-azido-4-hydroxypyrrolidin-1-yl]-2,2,2-trifluoroethan-1-one. Two sets of deoxyfluorination conditions are developed for achieving inversion of the chiral center with high or complete stereoselectivity.
Keywords: stereoselective; azides; deoxyfluorination; sulfuryl fluoride; pyrrolidines